Clinicopathological and Toxicological Evaluation of Drug-Induced Liver Injury in Medico-Legal Autopsy Cases - Fariha Tariq; Qurrat-ul-Ain Kamran; Rida Naseer; Obaid Anwar; Hafiz Muhammad Imran Aziz; Sabeen Irshad; Raazia Batool, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Drug-induced liver injury is a difficult diagnosis in medico-legal autopsy practice because exposure history, premortem biochemical data, histology, and toxicological findings may be incomplete or non-specific. Objective: To evaluate the clinicopathological and toxicological features of drug-induced liver injury in medico-legal autopsy cases and determine its contribution to death. Methods: This multicentre retrospective analytical study included 200 medico-legal autopsy cases examined at the Department of Forensic Medicine, King Edward Medical University, Lahore, and the Department of Forensic Medicine and Toxicology, Dera Ghazi Khan Medical College, from January 2024 to October 2025. Demographic data, exposure history, autopsy findings, liver histopathology, and multi-matrix toxicological results were reviewed. Cases were classified as probable, possible, or unlikely drug-induced liver injury through multidisciplinary assessment. Results: The mean age was 41.8 ± 15.2 years, and 118 cases (59.0%) were male. Paracetamol was the most frequently implicated agent, followed by antituberculous drugs, multidrug exposure, antiepileptics, antibiotics, and herbal preparations. Toxicological analysis was positive in at least one specimen in 166 cases (83.0%), with liver tissue showing the highest detection rate. Centrilobular or confluent necrosis was the predominant histopathological pattern. Overall, 108 cases (54.0%) were classified as probable and 62 (31.0%) as possible drug-induced liver injury. It was the primary cause of death in 79 cases (39.5%) and a contributory in 68 (34.0%). Conclusion: Postmortem diagnosis of drug-induced liver injury requires integrated interpretation of exposure history, autopsy findings, histopathology, toxicology, and exclusion of competing causes, rather than isolated findings.